PAPUA PROVINCE OF MSME DATA COLLECTION APPLICATION WITH LARAVEL FRAMEWORK - Amelia Ludia Kafiar; Remuz MB Kmurawak; Samuel Aleksander Mandowen (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: MSMEs are an essential sector in regional economic growth. Up to now, Papua Province has been trying to improve the economy. Still, it seems not optimal, as seen from the Human Development Index and the Percentage of the Poor Population, where Papua occupies the last rank. One of the causes found here is the processing of MSMEs that have not been optimal. MSME data collection services are still done manually with Microsoft Excel. This impacts making strategic policies for SMEs that are not optimal because their data are not updated. This study aims to develop a web-based MSME data collection application to facilitate the SME field admin and MSME actors for the data collection process. The method used in making this application is the waterfall method, where the development of this application is done sequentially. The final result of this study resulted in an easy application for collecting data on SMEs and updating data. In addition, it is also in the form of data collection reports for MSMEs and mapping of beneficiaries each year.           Keywords: Laravel Framework; UMKM Data Collection; Waterfall  Abstrak: UMKM merupakan sektor yang penting dalam pertumbuhan perekonomian daerah.  Selama ini Provinsi Papua berusaha meningkatkan perekonomian, namun terkesan belum optimal, dapat dilihat dari Indeks pembangunan Manusia serta Persentasi penduduk Miskin, dimana Papua menempati Posisi terakhir di Indonesia. Salah satu penyebab yang di temukan disini adalah pengolahan UMKM yang belum optimal. Pelayanan pendataan UMKM masih dilakukan secara manual dengan Microsoft Excel. Hal tersebut berdampak dalam pengambilan kebijakan strategis UMKM yang tidak optimal, karena data yang dimiliki tidak up to date. Penelitian ini bertujuan tunk mengembangkan aplikasi pendataan UMKM berbasis web untuk mempermudah admin bidang UKM maupun pelaku UMKM untuk proses pendataan. Metode yang digunakan dalam pembuatan aplikasi ini adalah metode waterfall, dimana pengembangan aplikasi ini lakukan secara berurutan. Hasil akhir penelitian ini menghasilkan aplikasi yang mudah untuk untuk pendataan UMKM  serta updating data. Selain itu juga berupa laporan pendataan UMKM dan juga pemetaan penerima bantuan setiap tahunnya.  Kata kunci: Framework Laravel; Pendataan UMKM; Waterfall,